2023
DOI: 10.1021/jacs.3c00914
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Reactivity of Copper(II) and Copper(III) σ-Aryl Intermediates in Aminoquinoline-Directed C–H Functionalization

Abstract: Over the past decade, numerous reports have focused on the development and applications of Cu-mediated C−H functionalization reactions; however, to date, little is known about the Cu intermediates involved in these transformations. This paper details the observation and characterization of Cu II and Cu III intermediates in aminoquinoline-directed C(sp 2 )−H functionalization of a fluoroarene substrate. An initial C(sp 2 )−H activation at Cu II occurs at room temperature to afford an isolable anionic cyclometal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…6 More recently, Sanford has reported the characterization of Cu III −aryl intermediates in aminoquinoline-directed C−H functionalization. 7 Despite significant progress in understanding the reductive elimination step in Cu catalysis, the involvement of Cu III species in Cu catalysis remains speculative. Particularly in Cu-catalyzed C(sp 3 ) cross-coupling reactions with alkyl radicals, an ongoing debate persists regarding the formation of Cu III species in these transformations.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 More recently, Sanford has reported the characterization of Cu III −aryl intermediates in aminoquinoline-directed C−H functionalization. 7 Despite significant progress in understanding the reductive elimination step in Cu catalysis, the involvement of Cu III species in Cu catalysis remains speculative. Particularly in Cu-catalyzed C(sp 3 ) cross-coupling reactions with alkyl radicals, an ongoing debate persists regarding the formation of Cu III species in these transformations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, Tilley recently published a study on Cu III metalla­cyclo­penta­diene dimer complexes, which can undergo reductive elimination to generate phenanthro­cyclo­buta­diene in quantitative yield . More recently, Sanford has reported the characterization of Cu III –aryl intermediates in amino­quinoline-directed C–H functionalization …”
Section: Introductionmentioning
confidence: 99%
“…, amides, imides, and sulfonamides (Scheme A,B). ,,, However, the aryl motif must be tethered to the Cu III center as a part of the macrocyclic ligand, which does not reflect the dynamic nature of copper–aryl bonds during coupling reactions. Likewise, Sanford et al recently reported a Cu II aryl complex with the aryl moiety linked to an aminoquinoline chelate . Treatment with oxidants results in aryl–aryl coupling or, when AgNO 2 is utilized as the oxidant, aryl–NO 2 coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Sanford et al recently reported a Cu II aryl complex with the aryl moiety linked to an aminoquinoline chelate. 23 Treatment with oxidants results in aryl−aryl coupling or, when AgNO 2 is utilized as the oxidant, aryl−NO 2 coupling. Warren et al reported a discrete copper(II) aryl complex capable of coupling with PhOH to generate Ar−OPh (Scheme 2C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 This approach, which allows for selectively replacing the hydrogen atoms on C-H bonds with more reactive functional groups (FG), has found wide applications in diverse fields such as pharmaceuticals and materials science. 10 Notable pioneers in C-H bond activation include Yu, 11 Murai, 12 White, 13 Sanford, 14 Fagnou, 15 and many others. Our group has focused on alkenyl C(sp 2 )-H bond functionalization.…”
Section: Introductionmentioning
confidence: 99%